KECERDASAN EMOSIONAL DAN SPIRITUAL DALAM AL-QUR’AN : (STUDI ANALISIS SURAT AL-ANBIYA) - Ghoni, Abdul (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
This research is focused on finding out how the prophet disseminate the emotional and spiritual intelligence as it is explained in al-Qur’an, especially in Surah al-Anbiya’. The using method is qualitative one by collecting data from several references in Tafsir. Besides, the researcher referred to some books related to the topic even from Islamic view or Western view. The researcher concluded that there are four ways to disseminate the emotional intelligence. Those ways are through self-control, praying toward God, admitting the mistakes and patience. Besides, in order to disseminate the spiritual intelligence, the researcher found that there are three ways of doing so, by having true knowledge especially it is about God, realizing that all great things are from God, and be closed to Him.